Reversible Soft Mechanochemical Control of Biaryl Conformations through Crosslinking in a 3D Macromolecular Network. (15th October 2020) - Kelber, Julien B.; Bensalah‐Ledoux, Amina; Zahouani, Sarah; Baguenard, Bruno; Schaaf, Pierre; Chaumont, Alain; Guy, Stephan; Jierry, Loïc
Abstract: Tuning the dihedral angle (DA) of axially chiral compounds can impact biological activity, catalyst efficiency, molecular motor performance, or chiroptical properties. Herein, we report gradual, controlled, and reversible changes in molecular conformation of a covalently linked binaphthyl moiety within a 3D polymeric network by application of a macroscopic stretching force. We managed direct observation of DA changes by measuring the circular dichroism signal of an optically pure BINOL‐crosslinked elastomer network. Stretching the elastomer resulted in a widening of the DA between naphthyl rings when the BINOL was doubly grafted to the elastomer network; no effect was observed when a single naphthyl ring of the BINOL was grafted to the elastomer network. We have determined that ca. 170 % extension of the elastomers led to the transfer of a mechanical force to the BINOL moiety of 2.5 kcal mol −1  Å −1 (ca. 175 pN) in magnitude and results in the opening of the DA of BINOL up to 130°. Abstract : Crosslinking BINOL derivatives in a 3D polymer network allows reversible tuning of the dihedral angle by macroscopic mechanical stretching of the material. This soft mechanotransduction was studied using simple and effective optical measurements of the host material and correlated with quantum molecular calculations and molecular dynamic simulations.